Pengaruh Gaya Hidup dan Literasi Keuangan Terhadap Rasionalitas Konsumsi Mahasiswa Pendidikan Ekonomi Angkatan 2022 Universitas Riau - Yusanra, Redi; Gusnardi, Gusnardi; Rizka, Mifta (Journal of Business Inflation Management and Accounting, 2025)
Increasing students' understanding of financial management is an important thing to do to improve students' rational consumption attitudes. Factors that influence the level of rationality of students' consumption rationality of students' consumption include internal and external factors, including lifestyle and financial literacy. Students who apply a lifestyle that is in accordance with their financial conditions and understand good financial literacy will always be rational in choosing goods to be consumed. The purpose of this paper is: 1) to determine how much influence lifestyle has on students' rational consumption, 2) to determine how much influence financial literacy has on students' rational consumption, and, 3) to determine how much influence lifestyle and financial literacy have on students' rational consumption. The data collection method used is a questionnaire. The independent variables in this study are lifestyle and financial literacy while the dependent variable is consumption rationality. The results of the study show that lifestyle and financial literacy together have a positive effect, this is indicated by the coefficient of determination (r2) of 0.568, it is also seen that the variables Lifestyle and Financial Literacy provide an effective contribution of 56.8% while the remaining 43.2% is influenced by other variables not included in the study. Thus, Lifestyle and Financial Literacy have a dominant influence with an effective contribution of 56.8% on the Consumption Rationality of Economic Education Students, class of 2022, University of Riau.